Thermal Effects in High-Power Laser Systems: Modeling and Mitigation - Aditya Sahu (International Journal of Manufacturing and Production Engineering, 2025)
High-power laser systems are increasingly employed in industrial manufacturing, defense, medical procedures, and scientific research due to their ability to deliver high energy density with excellent spatial coherence. However, the performance and reliability of these systems are significantly influenced by thermal effects arising from optical absorption, non-radiative recombination, and inefficient heat dissipation within laser gain media and optical components. These thermal phenomena lead to adverse effects such as thermal lensing, stress-induced birefringence, beam quality degradation, wavelength drift, and, in severe cases, catastrophic optical damage.This study presents a comprehensive modeling and mitigation framework for analyzing thermal effects in high- power laser systems. A coupled optical–thermal model is developed using heat transfer equations and laser rate equations to predict temperature distribution, refractive index variation, and induced mechanical stress under continuous-wave and pulsed operating conditions. Finite element analysis is employed to simulate thermal gradients in laser gain media and resonator components, enabling accurate estimation of thermal lens focal length and beam distortion. The modeling results are validated through comparison with reported experimental trends in high-power solid-state and fiber lasers.In addition to modeling, effective thermal mitigation strategies are investigated, including optimized heat sink design, advanced cooling techniques, selection of low-absorption optical materials, and resonator configuration optimization. The role of active thermal management, such as microchannel cooling and adaptive optics, is also discussed. The findings demonstrate that appropriate thermal control can significantly enhance beam quality, output power stability, and operational lifetime of high-power laser systems. This work provides valuable insights for the design and optimization of thermally robust laser systems for next-generation high-power applications.
Keywords: Finite element analysis; High-power laser systems; beam quality degradation; heat transfer modeling; thermal effects; thermal lensing